Impact of algal organic matter released from Microcystis aeruginosa and Chlorella sp. on the fouling of a ceramic microfiltration membrane. (15th October 2016) - Zhang, Xiaolei; Devanadera, Ma. Catriona E.; Roddick, Felicity A.; Fan, Linhua; Dalida, Maria Lourdes P.
Abstract: Algal blooms lead to the secretion of algal organic matter (AOM) from different algal species into water treatment systems, and there is very limited information regarding the impact of AOM from different species on the fouling of ceramic microfiltration (MF) membranes. The impact of soluble AOM released from Microcystis aeruginosa and Chlorella sp. separately and together in feedwater on the fouling of a tubular ceramic microfiltration membrane (alumina, 0.1 μm) was studied at lab scale. Multi-cycle MF tests operated in constant pressure mode showed that the AOM (3 mg DOC L −1 ) extracted from the cultures of the two algae in early log phase of growth (12 days) resulted in less flux decline compared with the AOM from stationary phase (35 days), due to the latter containing significantly greater amounts of high fouling potential components (protein and humic-like substances). The AOM released from Chlorella sp. at stationary phase led to considerably greater flux decline and irreversible fouling resistance compared with that from M. aeruginosa . The mixture of the AOM (1:1, 3 mg DOC L −1 ) from the two algal species showed more similar flux decline and irreversible fouling resistance to the AOM from M. aeruginosa than Chlorella sp. This was due to the characteristics of the AOM mixture being more similar to those for M. aeruginosa than Chlorella sp. The extent of the flux decline for the AOM mixture after conventional coagulation with aluminium chlorohydrate or alum was reduced by 70%. Graphical abstract: Highlights: The AOM from stationary phase caused greater fouling than the AOM from log phase. The AOM from Chlorella sp. caused greater fouling than that from Microcystis aeruginosa . The AOM mixture showed more similar fouling to the AOM from M. aeruginosa . Fouling by the AOM mixture after coagulation with ACH or alum was greatly reduced.